Answer:
y=-1x+-3
Step-by-step explanation:
Answer:
6,469!
Step-by-step explanation:
180-20=160
53-33=20
160*20=3,200
3,269+3,200=6,469
Answer:let me know please
Step-by-step explanation:
279/34 = 8.20588235294
But if you would like to round it up it would be 8.2 or 8.21 depending on what you'd like to round it up to.
Let me know if this is what you mean. If not, I will fix it! :)
Answer:
(f⋅g)(x)=8x^2−2x−15
Step-by-step explanation:
To find the expression (f*g)(x), multiply f(x) into g(x) using the distribution property.
(f*g)(x) = (2x - 3)(4x + 5) = 8x² - 12x + 10x - 15 = 8x² - 2x - 15